2009
DOI: 10.1089/ten.tea.2008.0630
|View full text |Cite
|
Sign up to set email alerts
|

Requirement of IFN-γ–Mediated Indoleamine 2,3-Dioxygenase Expression in the Modulation of Lymphocyte Proliferation by Human Adipose–Derived Stem Cells

Abstract: Human adipose-derived mesenchymal stem cells (hASCs) are mesenchymal stem cells (MSCs) with reduced immunogenicity and capability to modulate immune responses. Whereas the immunosuppressive activity of bone marrow-MSCs has received considerable attention during the last few years, the specific mechanisms underlying hASC-mediated immunosuppression have been poorly studied. Recent studies comparing both cell types have reported differences at transcriptional and proteomic levels, suggesting that hASCs and bone m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
212
1
6

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 258 publications
(247 citation statements)
references
References 50 publications
17
212
1
6
Order By: Relevance
“…However, in 2 separate studies the cell-cell contact requirement was corroborated [30] and disputed [31], respectively. Regardless of this disagreement, the immunosuppressive effect of ADSC has been consistently observed in all subsequent relevant studies [32][33][34][35][36]. Further, in a comparative study, ADSC and BMSC were found to exhibit the same pattern of immunologically relevant surface markers (MHC-I, MHC-II, CD40, and CD40L) [37].…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culturementioning
confidence: 81%
“…However, in 2 separate studies the cell-cell contact requirement was corroborated [30] and disputed [31], respectively. Regardless of this disagreement, the immunosuppressive effect of ADSC has been consistently observed in all subsequent relevant studies [32][33][34][35][36]. Further, in a comparative study, ADSC and BMSC were found to exhibit the same pattern of immunologically relevant surface markers (MHC-I, MHC-II, CD40, and CD40L) [37].…”
Section: Evidence For Adsc's Immunomodulatory Capacity: Cell Culturementioning
confidence: 81%
“…MSCs do not secrete immunomodulatory proteins in the absence of activation [4,5]. In vitro, activated T cells, individual or combinations of cytokines such as interferon-γ (IFNγ) or TNFα are used to activate MSCs [5].…”
Section: Msc Activation and Preconditioningmentioning
confidence: 99%
“…MSCs act as pleiotropic immune regulators to suppress immune responses through the production of multiple soluble factors and/or direct cell-cell contact in order to affect all the actors of immune responses: T cells, NK cells, B cells and DCs [4,28]. MSCs may act locally, however they may also accumulate in secondary lymphoid organs and attenuate delayed-type hypersensitivity response by inducing apoptotic cell death of surrounding immune cells in the draining lymph node.…”
Section: Msc Contact With Cells Of the Immune Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…MSCs employ these immunosuppressive effects via different soluble molecules including TGF-b, indoleamine 2,3-dioxygenase (IDO), inducible Nitric oxide synthases (iNOS), PGE2, IL-1 receptor antagonist and Tumour necrosis factor-inducible gene 6 (TSG6) [65][66][67][68]. Recently, other mechanisms of MSC-dependent immunomodulation have been described.…”
Section: Reduction Of Immune Cell Response and The End Of Inflammatormentioning
confidence: 99%